Dissemination of Genetically Improved Seed (Bangladesh, 2025) - Yeasin, Mohammed; Fakhruddin, Md.; Hamilton, Matthew (2025)
This dataset contains records of the 2025 sales of WorldFish G3 Rohu seeds by hatcheries across Bangladesh. It was developed from information provided directly by hatcheries involved in the large-scale dissemination of G3 Rohu and offers a solid basis for understanding its distribution and adoption. In addition, the dataset includes basic data on the genetic management of G19 GIFT by the EON Group, which received the improved GIFT germplasm from WorldFish Penang in 2025. This component documents the application of cohort-based mating schemes used by EON for broodstock multiplication, with the ultimate aim of large-scale seed production and dissemination.